Arbitrage opportunities and pricing efficiency in Malaysia futures market - Kuala Lumpur stock exchange composite index futures (FKLI) - Khong, Jason Jasmy (Universiti Malaysia Sarawak, (UNIMAS), 2013)
A futures contract is defined as the agreement between two parties, which are the seller and the buyer who agreed to purchase or sell a certain product. The contract states all the details of the transaction such as the agreed quantity, price and the delivery of the product on a predetermined date. Both parties have the responsibilities and obligations to carry out the agreed transaction at the maturity date. A futures contract is viewed as a hedging tool by the market players in order to minimize the risk exposure in cash market when there is adverse price change in the market. With the existence of stock indices futures contract, investors are now having a better control in managing their risk without changing their portfolio composition. In order to be a good hedging tool, hedging effectiveness is one the important criteria to measure the performance of the futures contract. It implies the accuracy of the futures contract to reflect its underlying market position. Therefore, pricing of the futures contract is very crucial because it will affect the hedging ability and performance of a future contract. Price convergence models indicates that price discrepancies between the cash market and future market should not last long. An effective arbitrage activity is vital to make sure. prices in both markets are moving in line. Arbitrageurs create a mechanism to ensure that. prices do not deviate substantially from its fair price for a long period of time. Therefore, if arbitrage is not effective, futures market will not be a good hedging tool for the investor. The general objective of this study is to identify the arbitrage opportunities and pricing efficiency for the Kuala Lumpur Stock Exchange Composite Index Futures (FKLI). The results show there are constant happenings of negative basis price deviations in the FKLI contracts under the simple cost of carry model. This confirms that there are many opportunities available for traders to undertake arbitrage activities. The results also suggest that the pricing mechanism is sensitive to the price volatility in the equity market. Moreover, there are still some violations of the arbitrage free boundary remained in observation after testing under different level of transaction costs which imply that the investor who is able to lower their transaction costs will have greater exploitation to the arbitrage opportunities than others.